A plugin for computing the pore/grain network tortuosity of a porous medium from 2D/3D MicroCT image. (March 2020) - Roque, Waldir L.; Costa, Richelieu R.A.
Abstract: Tortuosity is an important geometrical parameter of the pore or grain network in a porous medium. Here we present and discuss an implementation of a plugin to estimate the pore/grain network tortuosity of a porous medium sample. The tortuosity is estimated according to the geometric reconstruction algorithm that can be applied to 2D or 3D μCT image samples. To illustrate the tortuosity plugin features, applications are given i) for the 2D case: three synthetic image samples being one horizontal straight line, one diagonal straight line and a curved line, and additionally it is considered a Dolomite Silurian rock sample, ii) for the 3D case: the pore network of a Berea and Fontainebleau sandstone and a Grosmont carbonte reservoir core samples; the grain network of a distal-radius trabecular bone sample and, finally, the pore network of a Rhodic Ferralsol soil sample. Some comments and discussions about the tortuosity estimated with the current algorithm are also addressed.